Development of antibiotic loaded mesoporous bioactive glass and its drug release kinetics. Issue 4 (March 2020) - Anand, Akrity; Das, Piyali; Nandi, Samit Kumar; Kundu, Biswanath
Abstract: Aim of the study was to develop an efficient alternative for bone infections obtained during or after reconstruction surgeries using third generation antibiotic [ceftriaxone and sulbactam sodium (CFS)] loaded mesoporous bioactive glass (MBG) nanopowders. MBG nanopowders were prepared using cationic surfactant CTAB by wet chemical process, which gave spherical morphology (<125 nm), high surface area (473.2 m 2 /g) and pore volume (0.27 c.c./g). Antibiotic loading to powders was performed through vacuum infiltration followed by freeze drying process and loading efficiency was found to be 40.4% calculated from TGA, verified by CHN analysis ( 39%). Other characterizations like XRD, FTIR and EDX also confirmed successful encapsulation of antibiotics into MBG. Antibiotic release kinetics from nanopowders was studied up to7 days in contact with three different buffers (pH 1.2, 4.9 and 7.4) to understand pH dependency of intercalated system. Finally, both the systems have been further studied for antibiotic susceptibility assay by observing 'zone of inhibition' against gram positive and gram negative bacteria. We have found that variation in pH environment could slightly control antibiotics release kinetics in terms of clinical applications. We have noticed that CFS-MBG pallets were significantly able to inhibit both pathogens ( S. aureus and E. coli ) by creating clear 'zone of inhibition'. In contrast, visible presence of zone of inhibition was absent in case of bare MBG samples. However elution rate of CFS was initially high followed by sustained release can contribute for treatment of local bone infection and diseases.